Deficiency of filaggrin regulates endogenous cysteine protease activity, leading to impaired skin barrier function - Wang, X; Wang, J; Gutowska-Owsiak, D; Salimi, M; Selvakumar, T; Gwela, A; Chen, L; Wang, Y; Giannoulatou, E; Ogg, G (Wiley, 2017)
BACKGROUND: Atopic dermatitis (AD) is a common inflammatory skin disorder, characterized by skin barrier defects and enhanced allergen priming. Null mutations in the filaggrin gene (FLG) are strongly associated with moderate to severe AD, but the pathways linking barrier dysfunction and cutaneous inflammation are still largely unknown. AIM: To assess alteration of endogenous cysteine protease activity in FLG-deficient keratinocytes, and to determine whether the alteration in cysteine protease activity affects epidermal barrier function and associated gene and protein expression. METHODS: We established a stable FLG knockdown cell line, and reconstructed epidermal equivalents in vitro. Barrier function of the reconstructed epidermis, the barrier-associated genes and proteins, and the activity of endogenous cysteine proteases were tested. Inhibitors of cysteine proteases were used to further evaluate the role of endogenous cysteine proteases in epidermal barrier function. RESULTS: FLG knockdown induced impaired epidermal barrier function. Microarray, western blotting and fluorescence staining showed reduced expression of K10, ZO-1, E-cadherin, claudin-1 and occludin in FLG knockdown keratinocytes. Compared with cysteine protease activity in control cells, protease activity was dramatically enhanced in FLG knockdown keratinocytes. Furthermore, administration of cysteine protease inhibitors significantly recovered expression of K10 and tight junction proteins, and the barrier defect induced by FLG deficiency. CONCLUSIONS: This is the first observation of elevated endogenous cysteine protease activity in FLG-deficient keratinocytes, which may play an important role in impaired barrier function in AD skin. Modulation of cysteine protease activity might be a novel therapeutic approach for AD treatment.